A clinical comparison of 1-piece versus 2-piece implants: A systematic review and meta-analysis - de Oliveira Limírio, João Pedro Justino [UNESP]; Lemos, Cleidiel Aparecido Araújo [UNESP]; de Luna Gomes, Jéssica Marcela [UNESP]; Minatel, Lurian [UNESP]; Alves Rezende, Maria Cristina Rosifini [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Elsevier, 2019)
Statement of problem: One-step dental implant surgery with a 1-piece implant has been introduced with the aim of simplifying and increasing the effectiveness of treatment and providing greater comfort for the patient. Whether these goals have been met compared with conventional 2-piece implants remains unclear. Purpose: The purpose of this systematic review and meta-analysis was to compare the use of 1-piece versus 2-piece implants in terms of marginal bone loss and implant survival rate. Material and methods: This systematic review and meta-analysis adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and was recorded in the International prospective register of systematic reviews (PROSPERO) database (CRD 42018095721). A literature search was conducted in the PubMed/MEDLINE, Web of Science, and Cochrane Library databases for articles published up to May 2018. The population, intervention, comparison, outcome (PICO) question was, “Do patients who received 1-piece implants show similar marginal bone loss, survival rates, and complications as those who receive 2-piece implants?” Results: The meta-analysis was based on the Mantel-Haenszel and inverse variance methods. Implant survival rate was analyzed by using a dichotomous outcome, measured according to risk ratio (RR) and marginal bone loss by continuously evaluating the outcomes according to the mean difference (MD), both with a corresponding 95% confidence interval (CI). Five studies, including 270 participants with a mean age of 54.70 years and receiving 434 dental implants, were included. The mean follow-up period was 4 years. Meta-analysis did not reveal a significant difference in relation to implant survival rate (P=.85; RR: −0.89; CI: −0.27 to 2.98), as well as to marginal bone loss (P=.85; MD: −0.43; CI: −0.43 to −0.52). Conclusions: One- and 2-piece implants demonstrated effectiveness in the rehabilitation of patients requiring dental implants.